Phenolic composition of the berry parts of hybrid grape cultivar BRS Violeta (BRS Rubea×IAC 1398-21) using HPLC-DAD-ESI-MS/MS - Rebello, Ligia Portugal Gomes; Lago-Vanzela, Ellen Silva [UNESP]; Barcia, Milene Teixeira; Ramos, Afonso Mota; Stringheta, Paulo César; DaSilva, Roberto [UNESP]; Castillo-Muñoz, Noelia; Gómez-Alonso, Sergio; Hermosín-Gutiérrez, Isidro (Elsevier, 2013)
The grape is considered a major source of phenolic compounds when compared to other fruits and vegetables, however, there are many cultivars with distinct characteristics directly linked to phenolic profile. Thus, the present study aimed to identify and quantify, for the first time and in detail, the phenolic compounds present in the skin, flesh and seeds of BRS Violeta grape berry using combination of SPE methodologies and analytical HPLC-DAD-ESI-MS/MS. The study was extended to the different berry parts and the most important grape and wine phenolic families, and has revealed interesting features. Violeta grape has a very thick skin (46% of grape weight) that accumulated the most of grape phenolic compounds: great amount of anthocyanins (3930. mg/kg, as malvidin 3,5-diglucoside), together with also important amounts of flavonols (150. mg/kg, as quercetin 3-glucoside), hydroxycinnamic acid derivatives (HCAD; 120. mg/kg, as caftaric acid), and proanthocyanidins (670. mg/kg, as (+)-catechin); in contrast, it seems to be a low resveratrol producer. Violeta grape seeds accounted for similar proportions of low molecular weight flavan-3-ols (mainly monomers; 345. mg/kg, as (+)-catechin) and proanthocyanidins (480. mg/kg, as (+)-catechin). Violeta grape is a teinturier cultivar, but it only contained traces of anthocyanins and low amounts of all the other phenolic types in its red-colored flesh. The anthocyanin composition of Violeta grape was dominated by anthocyanidin 3,5-diglucosides (90%). Within flavonols, myricetin-type predominated and kaempferol-type was missing. In addition to expected hydroxycinnamoyl-tartaric acids, several isomeric esters of caffeic and p-coumaric acids with hexoses were tentatively identified, accounting for relevant proportions within the pool of HCAD. Although pending of further confirmation over successive vintages, the aforementioned results suggest that BRS Violeta grape cultivar could be considered an interesting candidate for the elaboration of highly colored and antioxidant-rich grape juices and wines. © 2013 Elsevier Ltd.
Keywords: Anthocyanins; BRS Violeta; Flavonols; Hybrid grape; Hydroxycinnamic acid; Phenolic compounds; Proanthocyanidins; Hybrid grapes; Hydroxycinnamic acids; Fruit juices; Fruits; Organic compounds; Phenols; Plants (botany)